The extraordinary adventures of Adele Blanc-Sec [videorecording (DVD)] - Besson, Luc; Amalric, Mathieu, 1965-; Bourgoin, Louise, 1981-; Lellouche, Gilles; Rouve, Jean-Paul, 1967-; Tardi, Jacques (Shout! Factory, 2010)
Adele, a redheaded, wisecracking, hard-living adventurer-cum-novelist living in pre-WWI France is on a mission in Egypt. She is attempting to retrieve a sarcophagus and tote it back to Western Europe. She succeeds on both fronts, but runs headfirst into another issue: a Parisian scientist with the power to heal Adele's comatose sister has accidentally let loose an ancient Pterodactyl above the Parisian skies. While a zany detective and a hunter attempt to eliminate the creature.